МОТИВАЦИИ ЛЕКСИЧЕСКИХ ТРАНСФОРМАЦИЙ (НА МАТЕРИАЛЕ ИСХОДНОЙ ЛЕКСЕМЫ ПРОЙТИ) - Król, Martyna (Acta Neophilologica, 2012)
The paper is aimed at the problem of transformational word-formation meant as a dynamic process of formation of new expressions on the basis of linguistic models using entire forms of already existing expressions, which become motivated expressions that way. This problem was taken into consideration from this viewpoint often defined in linguistics as polysemy. One lexical unit was analyzed on the basis of many core glossaries and a homonym dictionary, and three was an attempt to falsify the theory of polysemy and substitute it with the theory of homonimoidality seen as a phenomenon of formal similarity of expressions having different semantic features and retained derivational features (one of the expressions is a motivational one, another – motivated). The paper also presents a detailed description with a scheme of motivation of such lexical transformations of the entity, which is determined by a greater semantic elasticity. In the glossaries, the number of meanings for the lexical unit oscillated at 15–17 meanings but their definitions were different. The change in basic theory allowed both to distract and to order the semantic structure of homonimoids пройти.